2014
DOI: 10.1155/2014/104248
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Biodistribution Assessment of a Near Infrared-Labeled PSMA-Specific Small Molecule in Tumor-Bearing Mice

Abstract: Prostate cancer is the most frequently diagnosed cancer in men and often requires surgery. Use of near infrared (NIR) technologies to perform image-guided surgery may improve accurate delineation of tumor margins. To facilitate preclinical testing of such outcomes, here we developed and characterized a PSMA-targeted small molecule, YC-27. IRDye 800CW was conjugated to YC-27 or an anti-PSMA antibody used for reference. Human 22Rv1, PC3M-LN4, and/or LNCaP prostate tumor cells were exposed to the labeled compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…Additionally, we found that PSMA/GCPII is expressed throughout all parts of the mouse epididymis, as determined by immunohistochemistry. This agrees with previous findings, in which the researchers saw a strong signal in mouse epididymis after intravenous injection of a low‐molecular‐weight fluorescent agent targeting PSMA/GCPII . To investigate whether our observations may also be applicable to humans, we examined tissue sections of human epididymis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, we found that PSMA/GCPII is expressed throughout all parts of the mouse epididymis, as determined by immunohistochemistry. This agrees with previous findings, in which the researchers saw a strong signal in mouse epididymis after intravenous injection of a low‐molecular‐weight fluorescent agent targeting PSMA/GCPII . To investigate whether our observations may also be applicable to humans, we examined tissue sections of human epididymis.…”
Section: Discussionsupporting
confidence: 90%
“…This agrees with previous findings, in which the researchers saw a strong signal in mouse epididymis after intravenous injection of a low-molecular-weight fluorescent agent targeting PSMA/GCPII. 53,54 To investigate whether our observations may also be applicable to humans, we examined tissue sections of human epididymis. The presence of PSMA/GCPII mRNA in human epididymis has been reported.…”
Section: Psma/gcpii Is Highly Expressed In the Epididymismentioning
confidence: 99%
“…Fluorophores such as IRDye800 ® CW, VT680 ® , XenoLight CF680 and XenoLight CF750 have been used to label proteins (albeit different proteins) via NHS chemistry and the protein quality can be ensured by thin layer chromatography, HPLC or immune-binding assays [ 6 , 23 27 ]. The DOL which represents the number of fluorophore molecules conjugated to each molecule of Ab is a critical parameter that should be balanced for good in vivo signal, at the same time retaining the properties of Ab.…”
Section: Discussionmentioning
confidence: 99%
“…Kovar et al . described that YC-27-800CW showed good tissue contrast and tumor delineation at doses as low as 0.25 nmol 1. Subsequently, Neuman et al used a PCa murine model with subcutaneous PC3-PIP PSMA-expressing tumors to perform image-guided resection of tumor lesions 53.…”
Section: Psma-targeted Intraoperative Nirf Imagingmentioning
confidence: 99%
“…Despite recent improvements in imaging and therapy, PCa remains the most frequently diagnosed cancer type in men and is estimated to be the second leading cause of cancer related deaths 1, 2. Currently, PCa treatment is dependent on the stage of the disease at initial diagnosis.…”
Section: Introductionmentioning
confidence: 99%